Target organ damage in relation to intensity of cigarette smoking, statin therapy and the endogenous testosterone in middle aged hypertensive men with erectile dysfunction. (14th October 2021) - Angelis, A; Aggeli, K; Kakiouzi, V; Zisimos, K; Dimitroglou, I; Ioakeimidis, N; Georgakopoulos, C; Aznaourides, K; Vaina, S; Giannou, P; Synodinos, A; Verveniotis, A; et al.
Abstract: Background: Target organ damage (TOD) amplifies cardiovascular risk in essential hypertension. Erectile dysfunction (ED) refers to microvascular disease and frequently accompanies the hypertensive middle aged male population. Endogenous testosterone (TT) and statins exhibit vasoprotective effects while cigarette smoking typically relates to an adverse cardiovascular outcome. Purpose: To investigate TOD in relation to cigarette smoking, statin therapy and TT in essential hypertension middle aged males with ED. Methods: 223 hypertensive ED males (mean age: 59 yo) with no history of diabetes mellitus or overt cardiovascular disease enrolled the study. There were all screened for the presence of microalbuminuria, defined as urinary albumin loss 30 – 300 mg in a 24 h urine volume collection. Among them 96 (43%) were current cigarette smokers. Intensity of smoking referred in terms of packs per year. The presence and severity of ED was assessed by the SHIM-5 score (range 0–25), higher values indicate better erectile ability. All underwent a non invasive evaluation of the carotid – femoral pulse wave velocity (PWV), estimation of central pressures and augmentation index (AIx) a parameter of wave reflection amplification (Sphygmocor device).Moreover left ventricular mass index (LVMI) was assessed by 2D echocardiography (Devereux formula) and intima-media thickness (cIMT) of the common carotid artery by vascular ultrasound imaging. cIMT is a marker of atheromatosis. Results: Microalbuminuria detected in 89 (40%) patients was positively related to other parameters of TOD such as PWV, cIMT, LVMI (all p<0, 005) and smoking habits (p=0, 02) and negatively to the SHIM-5 score, TT and statin use (all p<0, 01). A notably negative correlation to the intensity of smoking was the SHIM-5 score (p=0, 013) and a positive the cIMT (p=0, 001). Statins were positively related to TT (p=0, 006).In linear regression analysis, relation of packs per year remained significant regarding microalbuminuria and the SHIM-5 after adjustment for age, body mass index, PWV, LVMI, central systolic, diastolic and pulse blood pressure. Similarly, relation of statins, TT and microalbuminuria remained significant after adjustment for age, LVMI, PWV, AIx and smoking status. Conclusion: Intensive cigarette smoking accelerates silent kidney damage and sabotages erectile performance in hypertensive middle aged men with ED independently of the central hemodynamic load. Statins protect from microvascular kidney damage and the decline of testosterone probably by enhancing endothelial physiology. In such population group, simple and clinically oriented criteria may reveal early diagnosis of target organ damage and guide appropriate life-style modifications and further therapeutic judgments. Funding Acknowledgement: Type of funding sources: None.